Rat bite fever in a patient with human immunodeficiency virus. (2022) - Bougioukas, Lauren; Vicks, Emily; Hale, Andrew J.; Dejace, Jean; Bullis, Sean
Abstract: The authors report the case of a 45-year-old male with history of human immunodeficiency virus who presented unresponsive and with injuries to his hands after spending a night on a lakeside beach. During his hospitalization, he developed a fever with arthralgias and was initially thought to have calcium pyrophosphate dihydrate crystal deposition disease before a diagnosis of Rat Bite Fever was ultimately discovered. He was successfully treated with six-weeks of ceftriaxone. The authors discuss the epidemiology, diagnosis, treatment, and prognosis of Rat Bite Fever.